PERBEDAAN EFEKTIFITAS PEMBERIAN TABLET FE PLUS JUS JAMBU BIJI MERAH DIBANDINGKAN DENGAN TABLET FE TERHADAP KADAR HEMOGLOBIN IBU HAMIL ANEMIA - Rini Rahmayanti; Ulvi Mariati; Nova Susilawati (STIKes MERCUBAKTIJAYA, 2019)
Anemia in pregnant women is very risky for the health of the mother and fetus. The incidence of anemia in pregnant women in Indonesia has increased from 2007 to 12.6% and to 37.1 in 2013. In West Sumatra Province, anemia in pregnant women was 43.1% in 2015. Anemia is usually characterized by a decrease in hemoglobin in mother's blood. To increase hemoglobin levels, pharmacological and non-pharmacological drugs can be used. One non-pharmacological treatment used is the administration of fruit juices. The purpose of this study was to determine the effectiveness of administration of Fe Plus tablet of Red Guava Juice on the Hemoglobin Levels of Pregnant Women with Anemia. Quasi-experimental research design using the two group design approach which was carried out on July 2 - 10, 2018 in the Working Area of ​​the Air Padang Children's Health Center. The sample consisted of 10 intervention groups and 10 control groups with a purposive sampling technique. Data analysis was performed univariately and bivariately using dependent T-tests. The results showed that the intervention group that was given Fe tablets before plus red guava juice was an average Hb of 9.55. After being given Fe tablets plus red guava juice an average Hb of 11.17 (th1,286 <tt1,859). The mean Hb levels of pregnant women in the control group were given Fe tablets of 8.84. The average Hb levels after being given Fe tablets for 7 days 11.48. There was no difference in the effectiveness of Fe Plus Tablets of Red Guava Juice compared with Fe Tablets on Hemoglobin Levels in Pregnant Women with Anemia. This study recommends that health workers be able to provide counseling about the benefits, risks, time consuming Fe tablets, side effects of Fe deficiency and ways to prevent iron deficiency. Keywords: Fe tablet, Guava Juice and Anemia, pregnant women